THE ROLE OF ORGANIZATIONAL COMMITMENT AS A MEDIATING VARIABLE IN THE INFLUENCE OF ORGANIZATIONAL CULTURE AND EMPLOYEE PERFORMANCE IN THE TELECOMMUNICATION INDUSTRY - Eka Putri Rifandani; Armanu Armanu; Raditha Dwi Vata Hapsari (Jurnal Aplikasi Manajemen, 2023)
Business competition has required every company to examine more deeply the appropriate strategy to use so that the company can have strong competitiveness and survive amidst quite dynamic environmental changes. Research on human resource management is expected to contribute to examining the contribution of elements that can be factors that affect employee performance. This current study examines and analyzes the effect of training and organizational culture on employee performance with the mediation of organizational commitment in the telecommunication industry. This current study focuses on mediating organizational commitment's effect on organizational culture and employee performance. One hundred ten respondents who participated in the survey were recruited by using a saturated sampling technique. The data of this quantitative study was analyzed using Structural Equation Modelling of PLS and hypothesis testing. This results study finds that the two variables have different effects: training has no significant effect on organizational commitment and employee performance, but organizational culture results in the opposite. Implications derived from this study are expected to be used by companies in their improvement efforts.